2015
DOI: 10.1017/s0272263114000825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Expanding and Equal Spacing on Second Language Vocabulary Learning

Abstract: Although expanding spacing is often regarded as the most effective practice schedule, studies comparing equal and expanding spacing have yielded mixed results. The present study set out to examine whether the amount of spacing and the retention interval may influence the effects of expanding and equal spacing on second language (L2) vocabulary learning. One hundred and twenty-eight Japanese college students studied 20 English-Japanese word pairs. The type of spacing (expanding and equal) and the amount of spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 44 publications
(232 reference statements)
11
103
0
1
Order By: Relevance
“…The investigation of lag effects (i.e., comparisons of two or more practice distributions varying in length) has been the focus of a small but growing number of SLA studies. Studies have begun to explore lag effects for L2 grammar learning (e.g., Bird, 2010;Rogers, 2015;Suzuki, 2017;Suzuki & DeKeyser, 2017a) and vocabulary learning (e.g., Nakata, 2015;Serrano & Huang, 2018), as well as general L2 proficiency in intensive versus extensive instructional programmes (e.g., Collins & White, 2011;Serrano & Muñoz, 2007).…”
Section: Distribution Of Practice Effects For L2 Grammar Learningmentioning
confidence: 99%
“…The investigation of lag effects (i.e., comparisons of two or more practice distributions varying in length) has been the focus of a small but growing number of SLA studies. Studies have begun to explore lag effects for L2 grammar learning (e.g., Bird, 2010;Rogers, 2015;Suzuki, 2017;Suzuki & DeKeyser, 2017a) and vocabulary learning (e.g., Nakata, 2015;Serrano & Huang, 2018), as well as general L2 proficiency in intensive versus extensive instructional programmes (e.g., Collins & White, 2011;Serrano & Muñoz, 2007).…”
Section: Distribution Of Practice Effects For L2 Grammar Learningmentioning
confidence: 99%
“…A number of cognitive psychology studies have been conducted to identify the most effective practice schedule (see Cepeda et al., for review). This line of investigation also has potential to enhance L2 learning, and the field has seen a surge of interest in this issue (Bird, ; Nakata, ; Nakata & Suzuki, ; Rogers, ; Serrano & Huang, ; Suzuki, ). The current special issue presents two innovative studies that further advance our understanding of the role of practice distribution.…”
Section: Defining and Extending Research Areas For L2 Practicementioning
confidence: 99%
“…The most comprehensive meta‐analysis showed that 259 out of 271 experiments supported the spacing effects (Cepeda et al., ). Spacing effects have been found in a number of learning domains, such as verbal learning in the first language (e.g., Dempster, ), in math (e.g., Rohrer & Taylor, ), in physics problems (e.g., Grote, ), and in L2 vocabulary learning (e.g., Bloom & Shuell, ; see Nakata, , for a recent review on spacing effects in L2 vocabulary learning).…”
Section: Introductionmentioning
confidence: 99%